An analysis of performance of an anaerobic fixed film biofilter (AnF2B) reactor in treatment of cassava wastewater - Prayitno, Prayitno; Rulianah, Sri; Zamrudy, Windi; Susilo, Sugeng Hadi (Eastern-European Journal of Enterprise Technologies, 2021)
The cassava starch wastewater contains organic materials (as BOD, COD) in high concentrations so it has the potential to cause pollution in the aquatic environment. Several methods of cassava starch wastewater treatment have been used to reduce the concentration of organic matter (pollutants) in cassava starch wastewater, including Activated Sludge, Stabilization Pond, Anaerobic-Aerobic filter process. However, various studies continue to be carried out to get higher processing efficiency on the factors that influence it. Several factors influence the efficiency of wastewater treatment processes, including the type and origin of decomposing microorganisms, hydraulic residence time (HRT), organic load rate (OLR), process design, pH, and temperature. The research aimed to evaluate the performance of the AnF2B reactor in treating cassava starch wastewater, in which the reactor performance is shown by changes in organic matter removal (COD removal) and biogas production. The research is conducted using 3 types of AnF2B reactors wherein each AnF2B reactor contains a bee nest-shaped bio-filter as a growth medium for the consortium of indigenous bacteria. The AnF2B reactor operates in anaerobic conditions with a set temperature of 29–30 °C and a pH of 4.5–7. In each AnF2B reactor, cassava starch wastewater is fed with different OLR so that each reactor has an HRT of 5, 6, and 7 days. The concentration of COD at the influent and effluent of the reactor was measured and the biogas was produced using the APHA standard method. The results showed that the AnF2B reactor had a satisfactory performance in COD removal and biogas production, which at HRT: 6 days and OLR of 1.72 g/L·day found that the maximum COD removal was 98 % and the volume of biogas of 4.8 L/L·day was produced on the 12th day